Pelatihan Pemanfaatan Social Media Tiktok Dalam Peningkatan Pendapatan UMKM Daivik Cell Menggunakan Aplikasi Bangbeli - Renanda Auresty Faradita; Maharani Ikaningtyas (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Credit and internet quota have now become the main needs of the community for smartphone users to communicate. As a form of community service, East Java "Veteran" UPN students participated in inviting and educating the UMKM Daivik Cell through utilizing the tiktok platform and joining to become partners of the bangbeli application with the aim of increasing income. The method used uses four stages, namely interviews, socialization, conducting training on the use of social media and the Bangbeli application, as well as monitoring and evaluation. The results obtained by Daivik Cell MSME players are that they know the importance of using tiktok and bangbeli applications which can increase income. In addition, the results of students being able to share existing knowledge by implementing it to UMKM Daivik Cell in developing their abilities in the field of business and marketing.